Penguatan Community Development Petani Nanas Desa Palaan melalui Digital Marketing - Lian Agustina Setiyaningsih; Muhammad Hanif Fahmi (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
Palaan Village, Kecamatan Ngajum, Kabupaten Malang, has a village superior product embryo, namely premium quality pineapple. At the same time it has an educational destination for pineapple villages. Pineapple farmers in Palaan have problems that often suffer losses when selling their harvests through middlemen. The problem of partners is divided into two: 1) conventional harvest sales, and 2) financial management is not yet able. Then the activities that can be carried out to answer these problems through digital marketing training by creating an online store for crop marketing. As well as providing knowledge and skills of a simple financial system application for managing crop yields. The results of this activity in the form of an online shop owned by a group of farmers managed by Karang Taruna and Bumdes. And a simple financial system application for pineapple farmers in Palaan Village. The use of this application, the marketing target is more extended to all regions in Indonesia.DOI: https://doi.org/10.26905/abdimas.v5i2.4361